(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Starting from the idea of language, French post-structuralist feminism separates itself as a specific current in contemporary literary theory during the seventies. This paper aims to present the key theoretical ideas of the French post-structuralist theoretician, Hélène Cixous, given in the essay The Laugh of the Medusa (1975), but also to make an intertextual liaison with her short autobiographical novel Reveries of the Wild Woman: Primal Scenes (2000). We read the novel as an autopoietic system closely intertwined with the critical thought of the author.